Using Raz-kids Reading Program to Enhance Fifth Grade EFL Omani Students’ Reading Comprehension Skills and Boost their Motivation - Al-Riyami, Zahra Suleiman Saif; Al-Siyabi, Salama Saif Hamed (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to evaluated the impact of Raz-kids program on the reading comprehension of fifth-grade students using a quasi-experimental design. A total of 64 students from Welayat Bidbid School in A’Dakhilia Governorate in the Sultanate of Oman, were divided into two groups: control and experimental. Over a two-month period, the experimental group used Raz-kids reading program daily at home, engaging in reading activities, listening exercises, and quizzes to enhance their reading skills. The findings indicated a noticeable improvement in reading comprehension scores, although it is not statistically significant, among participant students in the experimental group compared to the control group. Also, it was found that, the program positively influenced students’ motivation towards reading, with participants expressing a willingness to recommend it to their peers. These results suggest that Raz-kids program is an effective supplementary tool for improving reading comprehension and fostering positive attitudes towards reading among fifth-grade students.